Experimental statistics - Natrella, Mary Gibbons (National Bureau of Standards handbook ;, 2005)
This highly regarded handbook is perfect for those seeking engineering information and quantitative data for designing, developing, constructing, and testing equipment. Topics include characterizing and comparing the measured performance of a material, product, or process; general considerations in planning experiments; statistical techniques for analyzing extreme-value data; and more. 1966 edition. Index. Includes 52 figures and 76 tables.